Estratègies discursives en la poesia de Joan Vinyoli - Carbó, Ferran (Caplletra. Revista Internacional de Filologia, 2015)
This paper deals with some discoursive strategies that we can see in poetry. They are analized focusing on JoanVinyoli’s work, which presents characteristically the fiction of voices in discourse, various enunciative modalities, negation and adversativity.